PENGARUH KUALITAS LAYANAN YANG DIRASAKAN DAN LINGKUNGAN PELAYANAN TERHADAP KEPUASAN EMOSIONAL SERTA DAMPAKNYA PADA PERSEPSI PRODUK DAN NIAT BERPERILAKU DALAM KONTEKS UTILITARIAN SERVICE PADA PASIEN KLINIK SPESIALIS CEMPAKA LIMA BANDA ACEH - Zulfikar Salim, M. Ridha Siregar (Departemen Manajemen, 2017)
This research aims to understand how the impact of service quality and service environment towards patient emotional reaction, and how their perception towards the quality of product and their intentionof behave. Data’s are required from 123 clients who are visiting to Cempaka Lima Specialist Clinic in Banda Aceh City, Indonesia. The tool of data collective which is used in this research is questionnaire. Path analysis is used as the analysis method to know the direct effect of all variables in this research. Accoerding to path analysis and IBM SPSS 23 found that service quality, service environment, is significant affect emotional satisfaction, the next one is emotional satisfaction is significant affecting product perception and behavioral intention (I,e recommending,re-buying in the same place).Keyword: Service quality, service environment, emotional satisfaction, product perception and behavioral intention